Developing Fiqan as Islamic Education Learning Media for XI Grade Senior High School Students - Rohmat Hidayat; Moch Umar Faruq; Iin Baroroh Ma'arif (LPPM Universitas KH. A. Wahab Hasbullah, 2023)
This research aims to develop video animation-based learning media on the subjects of Islamic Religious Education Class XI high school. The results of this study are expected to help teachers in achieving PAI learning goals. In this study, the researchers adopted the Development Research (R&D) method through 5 stages of ADDIE development model, namely (1) Analyze, (2) Design, (3) Development, (4) Implementation, (5) Evaluation. . The data collection technique used is to use questionnaires and interviews that are analyzed descriptively. Based on the results of the validation of media experts and material experts stated that fiqan learning media can be judged worthy and interesting, so that the development of video animation-based media deserves to be used as a learning support media. The rest, this study can also be used as a reference for other researchers in developing PAI learning media at different levels.